Effectiveness of Photodynamic Therapy for the Inactivation of Candida spp. on Dentures: In Vitro Study - de Oliveira Mima, Ewerton Garcia; Pavarina, Ana Claudia [UNESP]; Ribeiro, Daniela Garcia; Dovigo, Lívia Nordi [UNESP]; Vergani, Carlos Eduardo [UNESP]; Bagnato, Vanderlei Salvador (Mary Ann Liebert, Inc., 2011)
Objective: This in vitro study evaluated the effectiveness of photodynamic therapy (PDT) for the inactivation of different species of Candida on maxillary complete dentures. Background data: The treatment of denture stomatitis requires the inactivation of Candida spp. on dentures. PDT has been reported as an effective method for Candida inactivation. Methods: Reference strains of C. albicans, C. glabrata, C. tropicalis, C. dubliniensis and C. krusei were tested. Thirty-four dentures were fabricated in a standardized procedure and subjected to ethylene oxide sterilization. The dentures were individually inoculated with one of the strains and incubated at 37 degrees C for 24 h. Dentures submitted to PDT (P + L +) were individually sprayed with 50 mg/L of Photogem (R) (PS) and, after 30 min, illuminated by LED light for 26 min (37.5 J/cm(2)). Additional dentures were treated only with PS (P + L-) or light (P-L +) or neither (P-L-). Samples of serial dilutions were spread on Sabouraud dextrose agar and incubated at 37 degrees C for 48 h. The colonies were counted and the values of log (cfu/mL) were analyzed by Kruskall-Wallis and Dunn tests (p < 0.05). Results: For all species of Candida, PDT resulted in significant reduction (p < 0.05) of cfu/mL values from dentures when compared with P-L-(reductions from 1.73 to 3.99 log(10)). Significant differences (p < 0.05), but lower reductions, were also observed for P + L-and P-L + when compared with P-L-for some species of Candida. Conclusions: PDT was an effective method for reducing Candida spp. on dentures.